1998
DOI: 10.1109/50.704614
|View full text |Cite
|
Sign up to set email alerts
|

Bandwidth of linearized electrooptic modulators

Abstract: Abstract-Many schemes have been proposed to make high dynamic range analog radio frequency (RF) photonic links by linearizing the transfer function of the link's modulator. This paper studies the degrading effects of finite transit time and optical and electrical velocity dispersion on such linearization schemes. It further demonstrates that much of the lost dynamic range in some modulators may be regained by segmenting and rephasing the RF transmission line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 12 publications
(20 reference statements)
0
14
0
1
Order By: Relevance
“…The suboctave DCM is a standard 2 2 DCM which has a length of one coupling length and has a dc bias point that minimizes the third-order intermodulation distortion [6]. Although quite sensitive to bias, our simulations have shown that the high SFDR of this modulator (approximately 138 dB) is quite insensitive to electrode loss.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…The suboctave DCM is a standard 2 2 DCM which has a length of one coupling length and has a dc bias point that minimizes the third-order intermodulation distortion [6]. Although quite sensitive to bias, our simulations have shown that the high SFDR of this modulator (approximately 138 dB) is quite insensitive to electrode loss.…”
Section: Resultsmentioning
confidence: 90%
“…Numerous variations of the modified DCM have been proposed [1]- [5]. Modeling of some of these linearized architectures showed that although the gain could have a broad frequency response, the SFDR bandwidth was limited by velocity mismatch [6], [7]. However, the earlier analyses did not include the effect of electrode loss on the transfer characteristics of the DCM.…”
Section: Introductionmentioning
confidence: 97%
“…These include linearizing the output of the EO modulator by pre-distorting the input signal or by linearizing the modulator itself by utilizing multiple modulators to subtract out some of the nonlinear effects of a single Mach-Zehnder device. Though such approaches have proven effective, these techniques typically have sub-octave bandwidths and result in a more complicated system [16].…”
Section: Discussionmentioning
confidence: 99%
“…5 Perhaps the most unique feature of EO polymer devices is their compatibility with a variety of substrates, such as Si, GaAs, or plastic. 6 Most of EO polymer modulators are based on the Pockels effect instead of the Kerr effect, as the quadratic electro-optic (QEO) coefficient is usually relatively much smaller than the Pockels coefficient. 7 In this paper, we report on an EO polymer waveguide modulator based both on the Pockels effect and the Kerr effect.…”
Section: Introductionmentioning
confidence: 99%